A Journey Around the Different Scales Involved in the Description of Matter and Complex Systems A Brief Overview with Special Emphasis on Kinetic Theory Approaches - Chinesta, Francisco (SpringerBriefs in Applied Sciences and Technology,, 2018)
This SpringerBrief covers the main scales of description of matter, starting at its finest level, the quantum scale, moving through ab-initio, molecular dynamics, coarse grained approaches, to finish at the scale of kinetic theory models that allows a nice compromise between the rich but expensive microscopic descriptions and the computationally cheap but sometimes too coarse macroscopic descriptions. The book addresses undergraduate and graduate students, as well as beginners in multi-scale modeling of materials.